Thinking Like a Trader: The Impact of Neoliberal Doctrine on Habits of Thought. Issue 2 (2nd April 2016) - Duroy, Quentin
Abstract: Neoliberalism has come out of the financial crisis unscathed. Moreover, it has further asserted its dominance over geopolitical discourse and ideology worldwide. I contend that neoliberal supremacy in the policy arena and upon domestic and international institutions has been largely uncontested because it has penetrated all aspects of life to the extent that it now represents what Thorstein Veblen referred to as "the modern point of view." Understanding the global power of neoliberalism requires examining not only its well-established hegemony over institutions as social constructs, but also its impact on habits of thought as mental constructs. From a Veblenian perspective, I argue that the neoliberal doctrine generates habits of thought which legitimize the transformation of a marketoriented economy into a full-fledged market society. The impact of the normalization of the neoliberal mode of behavior may, in the end, worsen the fracture between nation and state and unravel the fabric of society by justifying fully detached, emotion-free, and self-centered actions that crowd-out pro-social behaviors and challenge any social conception of the common good.